2272. High Interest in Doxycycline for Sexually Transmitted Infection Post-Exposure Prophylaxis (Doxy-PEP) in a Multi-city Survey of Men Having Sex With Men (MSM) Using a Social-Networking App. (26th November 2018) - Spinelli, Matthew A; Scott, Hyman; Vittinghoff, Eric; Liu, Albert Y; Coleman, Kenneth; Gandhi, Monica; Buchbinder, Susan P
Abstract: Background: Sexually transmitted infections (STI) in people living with HIV (PLWH) and HIV-uninfected men who have sex with men (MSM) are increasing. Doxycycline post-exposure prophylaxis (doxy-PEP) showed partial efficacy against STI acquisition in a small population of HIV-uninfected MSM using pre-exposure prophylaxis (PrEP). Acceptability in a larger, diverse population of MSM is unknown. Methods: We conducted a survey of doxycycline for STI PEP among users of a gay social networking app in 6 US cities: Atlanta, Birmingham, Chicago, New York City, San Francisco, and Seattle. In adjusted analyses using logistic regression, we examined factors associated with bacterial STI in the last year and willingness to use doxy-PEP. Predictors included: demographics, city, risk behaviors, and bacterial STI. Results: Overall, 1301 individuals, 80% HIV-uninfected, 16% PLWH, and 4% status unknown responded to the survey. The median age was 33 and the sample was racially/ethnically diverse: 7% Asian, 21% Black, 24% Latinx, and 44% White. Most (80%), reported condomless sex in the last 6 months; 39% reported an STI in the last year. Of the HIV-uninfected, 44% were on PrEP. In adjusted analysis, age per ten years was inversely associated with an STI in the last year (AOR 0.8; 95% CI: 0.7–0.9 and AOR 0.2; 0.0–0.8 respectively), while number of partners in the last 6 months and condomless anal sex were associated with STI (AOR 1.1 per 5 partners; 1.0–1.1 and AOR 3.8; 2.5–5.8 respectively). There was no difference by race/ethnicity, or when comparing PrEP users to PLWH, however not using PrEP was inversely associated with STI (AOR 0.2; 0.2–0.3). Overall, 84% of respondents were interested in trying doxy-PEP. The factors associated with higher interest were: older age per ten years (1.2; 95% CI 1.0–1.4), Black race and Latinx ethnicity vs. White race (AOR 2.0; 1.2–3.5 and 1.9; 1.2–3.0 respectively), prior STI (AOR 1.7; 1.1–2.5), and having condomless sex (AOR 1.6; 1.1–2.4). Interest did not differ by city, number of partners, serostatus, or PrEP use. Conclusion: Interest in doxy-PEP was high among a diverse population of MSM in the US Differences in reported STI prevalence may be related to increased detection through screening in PLWH and on PrEP. Additional research to evaluate efficacy/safety of doxy-PEP is needed to potentially reduce STIs among MSM. Disclosures: All authors: No reported disclosures.